Del parque urbano al parque sostenible. Bases conceptuales y analíticas para la evaluación de la sustentabilidad de parques urbanos - Vélez Restrepo, Luis Aníbal (Revista de Geografía Norte Grande, 2021)
The environmental functions of urban parks have become a basic question, a target for urban management. However, the analysis and environmental management of such spaces is usually done by various institutional sectors without consideration of array in terms of its contribution to urban sustainability. The aim of the following paper is to develop a model for evaluating big urban parks sustainability, as a starting point for its analysis and integrated environmenta management. A conceptual and analytic structure is defined, which is made up of three principles and nine indicators. The model is showed as a conceptúa and methodological contribution; and as a management tool, from an opened model, flexible, that accepts the changing of indicators or the adding of others, according to the specific conditions